2022
DOI: 10.1021/acs.jafc.2c06516
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Virtual Screening of Natural Products and Optimization for the Design and Synthesis of Novel CeCht1 Inhibitors as Nematicide Candidates

Abstract: Nematode chitinases are critical components of the nematode life cycle, and CeCht1 is a potential target for developing novel nematicides. Herein, lunidonine, a natural quinoline alkaloid, was first discovered to have inhibitory activity against CeCht1, which was acquired from a library of over 16,000 natural products using a structure-based virtual screening methodology. A pocket-based lead optimization strategy was employed based on the predicted binding mode of lunidonine. Subsequently, a series of benzo[d]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…MD simulations were performed by using AMBER (version 18.0). Ac -AChBP and the target compound complexes were simulated with reference to previous methods. , The AMBER ff99SB force field was used for the protein, while the general AMBER force field was used for the ligand. All data were collected over an MD simulation trajectory of 50 ns.…”
Section: Methodsmentioning
confidence: 99%
“…MD simulations were performed by using AMBER (version 18.0). Ac -AChBP and the target compound complexes were simulated with reference to previous methods. , The AMBER ff99SB force field was used for the protein, while the general AMBER force field was used for the ligand. All data were collected over an MD simulation trajectory of 50 ns.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to their structural diversity, unique mechanisms of action, and good environmental compatibility, natural products have provided synthetic templates for the creation of small-molecule drugs with medicinal and pesticide properties. However, most bioactive natural product leads are difficult to directly formulate into drugs because of their low natural content, complex and unstable structures, complicated chemical syntheses, and weak biological activities. Therefore, extracting the main molecular skeleton and modifying its structures, especially with groups with excellent pharmacological activity, can enhance the pharmacological activity of natural products. Flavonoids are widely present in secondary metabolites of plants and microorganisms and used as template structures for drug discovery due to their broad and diverse activities, such as antibacterial, antifungal, antiviral, antioxidant, antitumor, and anti-inflammatory (Figure ). The 4 H -chromen-4-one core obtained by simplification of flavonoids can be optimized and modified, and the rational design can enhance the pharmacological activities of chromones. For example, some chromone derivatives bearing dithiocarbamate, 1,3,4-thiadiazole/oxadiazole, amide, thioether, 1,2,4-triazole, and Schiff base fragments have been successfully constructed and evaluated as potentially novel antimicrobial agents (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the multitarget approach has been considered a promising strategy for future pest control because single-target pesticides have a high risk of leading to the development of resistance. , Recently, our group has been focusing on novel IGRs with new mechanisms, and found a class of heptacyclic pyrazolamide derivatives as a dual-target IGRs candidate that act on both EcR and Of ChtI with excellent insecticidal activity, , illustrating that the multitargeting strategy facilitates bioactivity. In our latest study, we found that compound a12 displayed certain inhibitory activities against Of ChtI (66.5%), Of ChtII (68.9%), and Of Chi-h (89.2%) at 100 μM (Table S1) and is a potential multitarget inhibitor for further exploration for highly active multichitinase inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…In our latest study, we found that compound a12 displayed certain inhibitory activities against Of ChtI (66.5%), Of ChtII (68.9%), and Of Chi-h (89.2%) at 100 μM (Table S1) and is a potential multitarget inhibitor for further exploration for highly active multichitinase inhibitors. 27 In this study, the binding modes of the lead compound a12 with three chitinases Of ChtI, Of ChtII, and Of Chi-h were firstly investigated to identify the pivotal interactions and residues necessary for inhibitory activities. Subsequently, based on the characteristics of the key residues in the active pockets, the structural optimization on a12 was performed to rationally design and synthesize novel multichitinase inhibitors with high…”
Section: ■ Introductionmentioning
confidence: 99%